PENGARUH CITRA MEREK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE DI KALANGAN MAHASISWA - Handaruwati, Indah (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2023)
This study aims to provide empirical evidence of the influence of brand image, price and promotion either partially or simultaneously on purchase decision of samsung brand mobile phones among Surakarta Christian University students. The population in this study were all active students while the sample was taken by purposive sampling as many as 100 students. The results showed that brand image was positive but not significant. So that the brand image variable cannot stand alone partially, the price has significant effect and the promotion has positive but not significant. Together or simultaneous brand image, price and promotion variables have a significant effect.